Identity threats and ideas of superiority as drivers of religious violence? Evidence from a survey experiment in Dar es Salaam, Tanzania. (May 2022) - Basedau, Matthias; Gobien, Simone; Hoffmann, Lisa
Religion has become increasingly contentious in recent years. Faith-based discrimination, hostility and violence seem to have increased worldwide. But how can faith lead to conflict? In this article, we test the impact of two important dimensions of religion that have been neglected in previous research: the belief in 'one true religion' and perceptions of threats by other religious groups. Putting these two potential drivers to the test, we conducted a representative survey experiment with 972 respondents in Dar es Salaam, Tanzania. Results show that one of the tested dimensions, perceptions of threats by others, increases the support to use violence to defend one's own group. This is particularly the case for religiously intolerant respondents with characteristics such as pre-existing threat perceptions, unfavorable views on intermarriage, or belief in the superiority of their own faith. In contrast, we find relatively weak evidence that the prime of 'one true religion' increases the readiness to use violence. Our findings have important implications for policy: We conclude that appeals by leaders to threats by others and intolerance toward other faiths can contribute to more conflict. Political and religious leaders should refrain from capitalizing on such notions and should promote tolerance towards other faiths instead.